Technology in Field Education: Managing Ethical Issues. Issue 2 (3rd July 2019) - Barsky, Allan
Abstract: Given the growing importance of technology in social work practice, field educators need to prepare students for the competent and ethical use of technology. This article explores ethical concerns that field instructors should address with students, including confidentiality, professional boundaries, interjurisdictional practice, client safety, and the impact of private conduct on professional practice.